2022
DOI: 10.1002/lpor.202100300
|View full text |Cite
|
Sign up to set email alerts
|

Topological Photonic Crystals: Physics, Designs, and Applications

Abstract: Recent research in topological photonics has not only proposed and realized novel topological phenomena such as one-way broadband propagation and robust transport of light, but also designed and fabricated photonic devices with high-performance indexes, which are immune to fabrication errors such as defects or disorders. Photonic crystals, which are periodic optical structures with the advantages of good light field confinement and multiple adjusting degrees of freedom, provide a powerful platform to control t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(70 citation statements)
references
References 418 publications
(846 reference statements)
0
70
0
Order By: Relevance
“…The topological invariant of the VPC is defined as the valley Chern number, C V = C K −C K , where C K is the integral of Berry curvature around K point [4]. Further, we calculate the Berry curvature of the DPC, as shown in Fig.…”
Section: Valley Photonic Crystalsmentioning
confidence: 99%
“…The topological invariant of the VPC is defined as the valley Chern number, C V = C K −C K , where C K is the integral of Berry curvature around K point [4]. Further, we calculate the Berry curvature of the DPC, as shown in Fig.…”
Section: Valley Photonic Crystalsmentioning
confidence: 99%
“…In recent years, there has been an increasing interest in topological photonics which supports unidirectional electromagnetic wave propagation and show robustness against backscattering, disorders, and defects [ 1 , 2 , 3 , 4 , 5 ]. Researchers have found that one-way edge modes can appear in valley PCs and magneto-optical photonic crystals (MOPCs) [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increasing interest in topological photonics which supports unidirectional electromagnetic wave propagation and show robustness against backscattering, disorders, and defects [ 1 , 2 , 3 , 4 , 5 ]. Researchers have found that one-way edge modes can appear in valley PCs and magneto-optical photonic crystals (MOPCs) [ 2 , 3 , 4 ]. Among them, MOPCs provide an important platform for studying the generation and transport properties of topological photonic states (TPSs) by breaking time-reversal symmetry via a dc external magnetic field (EMF), which can be seen as a one-way mode [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among all these topological systems, the systems relying on the valley Hall effect [53,54] are very promising for experimental realization of topological edge solitons, since they do not require sophisticated longitudinal modulations of the refractive index landscapes leading to additional losses as in Floquet systems [26,27,28,29,30,31,32,33,34,55] or external or artificial magnetic fields as in structured polariton microcavities [41,42,43,44]. In valley Hall systems edge states emerge on the domain wall between two lattice regions due to breaking of the in-version symmetry of the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…In valley Hall systems edge states emerge on the domain wall between two lattice regions due to breaking of the in-version symmetry of the lattice. This symmetry breaking can be achieved, for example, by introducing different detuning into depths of lattice channels at both sides of the domain wall [53,54]. So far, only scalar bright and dark [35,36,37,56] or specific Dirac [57] edge solitons were encountered in valley Hall photonic systems.…”
Section: Introductionmentioning
confidence: 99%